2019
DOI: 10.1055/s-0039-1692697
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Ovarian Reserve of Different Hemostasis Methods in Laparoscopic Cystectomy: A Systematic Review and Meta-analysis

Abstract: Objective The objective of this review was to analyze the impact on ovarian reserve of the different hemostatic methods used during laparoscopic cystectomy. Data Sources The studies were identified by searching electronic databases (MEDLINE, Embase, Cochrane, LILACS) and scanning reference lists of articles. Methods of Study Selection We selected clinical trials that assessed the influence of hemostatic techniques on ovarian reserve in patients with ovarian cysts with benign sonographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…The traditional hemostatic technique is bipolar coagulation, but it might be used with caution to avoid excessive compromise of ovarian reserve [ 8 , 38 ]. A recent systematic review and meta-analysis comparing this approach with suture, ultrasonic energy and intra-ovarian hemostatic sealants showed a lower impact in postoperative AMH levels with the use of suturing [ 39 ]. The same result was achieved in a previous meta-analysis comparing just bipolar coagulation vs. suture [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The traditional hemostatic technique is bipolar coagulation, but it might be used with caution to avoid excessive compromise of ovarian reserve [ 8 , 38 ]. A recent systematic review and meta-analysis comparing this approach with suture, ultrasonic energy and intra-ovarian hemostatic sealants showed a lower impact in postoperative AMH levels with the use of suturing [ 39 ]. The same result was achieved in a previous meta-analysis comparing just bipolar coagulation vs. suture [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…76 When comparing bipolar with haemostatic sealants, the results favoured the use of haemostatic agents. 76 Recommendations for ovarian cystectomy…”
Section: Effect Of Surgical Technique On Fertility Outcomesmentioning
confidence: 99%
“…Following cystectomy, haemostasis can be achieved using diathermy, suturing or haemostatic sealants. A systematic review and meta‐analysis of 12 published controlled trials showed that laparoscopic suturing was superior to bipolar coagulation when comparing AMH and AFC – even 12 months after surgery 76 . When comparing bipolar with haemostatic sealants, the results favoured the use of haemostatic agents 76 …”
Section: Effect Of Surgical Technique On Fertility Outcomesmentioning
confidence: 99%
“…Ще однією перспективною методикою збереження оваріального резерву є PRP-терапія з аутологічної крові. Плазма, збагачена тромбоцитами (platelet rich plasma -PRP), являє собою концентроване джерело тромбоцитів, отримане з венозної крові після її центрифугування [73]. Цей концентрат як унікальна система містить в собі понад 800 типів білкових молекул, цитокінів, гормонів і хемоатрактантів [74].…”
Section: акушерство та гінекологіяunclassified